Toughened Hydrogels for 3D Printing of Soft Auxetic Structures. Issue 19 (31st August 2022) - Pruksawan, Sirawit; Chee, Heng Li; Wang, Zizhen; Luo, Ping; Chong, Yi Ting; Thitsartarn, Warintorn; Wang, FuKe
Abstract: Materials with negative Poisson's ratio have attracted considerable attention and offered high potential applications as biomedical devices due to their ability to expand in every direction when stretched. Although negative Poisson's ratio has been obtained in various base materials such as metals and polymers, there are very limited works on hydrogels due to their intrinsic brittleness. Herein, we report the use of methacrylated cellulose nanocrystals (CNCMAs) as a macro‐cross‐linking agent in poly(2‐hydroxyethyl methacrylate) (pHEMA) hydrogels for 3D printing of auxetic structures. Our developed CNCMA‐pHEMA hydrogels exhibit significant improvements in mechanical properties, which is attributed to the coexistence of multiple chemical and physical interactions between the pHEMA and CNCMAs. Structures printed by using CNCMA‐pHEMA hydrogels show auxetic behavior with greatly enhanced toughness and stretchability compared to the hydrogel with a traditional cross‐linking agent. Such strong and tough auxetic hydrogels would contribute toward establishing advanced flexible implantable devices such as biodegradable oesophageal self‐expandable stents. Abstract : The development of tough and stretchable hydrogels for 3D printing of auxetic structures is reported. The use of multi‐functional macro‐cross‐linking agents could significantly enhance the toughness of hydrogels due to the formation of multiple chemical and physical cross‐links. Re‐entrant hexagonal structures printed by using these hydrogels show auxetic behavior with improved mechanical performance and potential for use as medical devices.